Immunogenicity and safety of a quadrivalent inactivated influenza vaccine in children 6–59 months of age: A phase 3, randomized, noninferiority study. Issue 2 (7th January 2019) - Statler, Victoria A.; Albano, Frank R.; Airey, Jolanta; Sawlwin, Daphne C.; Graves Jones, Alison; Matassa, Vince; Heijnen, Esther; Edelman, Jonathan; Marshall, Gary S.
Abstract: Background: In the Southern Hemisphere 2010 influenza season, Seqirus' split-virion, trivalent inactivated influenza vaccine was associated with increased reports of fevers and febrile reactions in young children. A staged clinical development program of a quadrivalent vaccine (Seqirus IIV4 [S-IIV4]; Afluria® Quadrivalent/Afluria Quad™/Afluria Tetra™), wherein each vaccine strain is split using a higher detergent concentration to reduce lipid content (considered the cause of the increased fevers and febrile reactions), is now complete. Methods: Children aged 6–59 months were randomized 3:1 and stratified by age (6–35 months/36–59 months) to receive S-IIV4 (n = 1684) or a United States (US)-licensed comparator IIV4 (C-IIV4; Fluzone® Quadrivalent; n = 563) during the Northern Hemisphere 2016–2017 influenza season. The primary objective was to demonstrate noninferior immunogenicity of S-IIV4 versus C-IIV4. Immunogenicity was assessed by hemagglutination inhibition (baseline, 28 days postvaccination). Solicited, unsolicited, and serious adverse events were assessed for 7, 28, and 180 days postvaccination, respectively. Results: S-IIV4 met the immunogenicity criteria for noninferiority. Adjusted geometric mean titer ratios (C-IIV4/S-IIV4) for the A/H1N1, A/H3N2, B/Yamagata, and B/Victoria strains were 0.79 (95% CI: 0.72, 0.88), 1.27 (1.15, 1.42), 1.12 (1.01, 1.24), and 0.97 (0.86, 1.09), respectively. Corresponding values for differences in seroconversion rates (C-IIV4 minus S-IIV4) were −10.3 (−15.4, −5.1), 2.6 (−2.5, 7.8), 3.1 (−2.1, 8.2), and 0.9 (−4.2, 6.1). Solicited, unsolicited, and serious adverse events were similar between vaccines in both age cohorts, apart from fever. Fever rates were lower with S-IIV4 (5.8%) than C-IIV4 (8.4%), with no febrile convulsions reported with either vaccine during the 7 days postvaccination. Conclusion: S-IIV4, manufactured with a higher detergent concentration, demonstrated noninferior immunogenicity to the US-licensed C-IIV4, with similar postvaccination safety and tolerability, in children aged 6–59 months. This completes the program demonstrating the immunogenicity and safety of S-IIV4 in participants aged 6 months and older. Funding: Seqirus Pty Ltd;ClinicalTrials.gov identifier: NCT02914275 .